1987
DOI: 10.1139/v87-361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of steric hindrance in molecules of substituted 2-phenyl-1,1,3,3-tetramethylguanidines on the kinetics and isotope effects of their proton transfer reactions with 4-nitrophenylnitromethane in acetonitrile solvent

Abstract: PRZEMYSLAW PRUSZYNSKI. Can. J. Chem. 65, 2160Chem. 65, (1987. Rate constants have been determined for the proton and deuteron transfer reactions of 4-nitrophenylnitromethane, NO2C6H4CH2NO2, with three phenyl substituted derivatives of 2-phenyl-l , l,3,3-tetramethylguanidine, X-C6H4-N= C[N(CH3)2]2, where X = 4-C1,2-C1, and 2-Br, in the temperature range 278-308 K in acetonitrile solvent. In the concentration ranges used, the reaction to form an ion-paired product is first order in acid and first order in base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Since then steric hindrance has been regarded as one of the most important factors leading to increased deuterium KIEs. [6][7][8] In further studies, even though they were designed to find an increase in the KIE due to steric hindrance, it was found that steric hindrance in both the base and C-acid may actually reduce the KIE. 9,10 However, bulky substituents not only cause repulsive interactions in the transition state, they can also change other parameters influencing the KIE, such as ∆GЊ, so the discussion of steric effects is doomed to be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Since then steric hindrance has been regarded as one of the most important factors leading to increased deuterium KIEs. [6][7][8] In further studies, even though they were designed to find an increase in the KIE due to steric hindrance, it was found that steric hindrance in both the base and C-acid may actually reduce the KIE. 9,10 However, bulky substituents not only cause repulsive interactions in the transition state, they can also change other parameters influencing the KIE, such as ∆GЊ, so the discussion of steric effects is doomed to be difficult.…”
Section: Introductionmentioning
confidence: 99%